2021
DOI: 10.1007/s00402-021-03871-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patella height after patella fracture on clinical outcome: a 13-year period

Abstract: Introduction The incidence of patella fracture is statistically low (0.5–1.5%) compared to other fractures of the extremities [Patella fractures 76(10):987–997, 2005]. In the latter research, patella fractures if treated surgically present an overall inferior functional outcome. Little is known about the influence of the postoperative patella height on the clinical outcome. Therefore, the aim of our study was to analyse the influence of the patella height on the patients’ functional outcome after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Although there are studies reporting patella baja after patella fracture in the literature, there is no study reporting an elongated patella case. After a patella fracture, the reported Patella Baja rate is up to 43.9% (22,23). Our rate of patella baja (16.7%) is within this limit.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although there are studies reporting patella baja after patella fracture in the literature, there is no study reporting an elongated patella case. After a patella fracture, the reported Patella Baja rate is up to 43.9% (22,23). Our rate of patella baja (16.7%) is within this limit.…”
Section: Discussionsupporting
confidence: 52%
“…Our rate of patella baja (16.7%) is within this limit. It has also been reported that patella baja does not affect clinical results in the short term (22).…”
Section: Discussionmentioning
confidence: 88%
“…It is well known that patella baja can occur after operative treatment for patellar fracture; however, the correlative factors for patella baja have been surprisingly poorly investigated. Sebastian et al [3] investigated patellar height after patellar fracture with a mean follow-up of 503.8 days. They found 20% and 14.5% of all enrolled patients had patella baja and alta, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Patellar fractures are a relatively common type of fracture, accounting for approximately 1% of all fractures [1,2]. Their peak incidence occurs during the third to sixth decades of life [3]. Operative treatment is required for about 30% of injured patients, with the primary indication being intra-articular incongruity exceeding 2 mm and loss of the knee joint's extensor mechanism [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation